2001
DOI: 10.1177/088307380101601002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cerebral Maturation by Visual and Quantitative Analysis of Resting Electroencephalography in Children With Primary Nocturnal Enuresis

Abstract: This study was undertaken to evaluate resting electroencephalographic (EEG) changes and their relations to cerebral maturation in children with primary nocturnal enuresis. Cerebral maturation is known to be important in the pathogenesis of this disorder. Twenty-five right-handed patients with primary nocturnal enuresis, aged 6 to 14 years, and 23 age- and sex-matched healthy children were included in this cross-sectional case-control study. The abnormalities detected using such techniques as hemispheral asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…In regard to the latter, readers may find it interesting that children in special education classes, which is a population we often see in neurotherapy, have more problems with nocturnal enuresis than other children (Spee van der Wekke, Hirasing, Meuhmeester, & Badder, 1998). I do not believe that neurofeedback practitioners have been aware that there are also some interesting QEEG studies on primary nocturnal enuresis (e.g., Kaada & Betvedt, 1981;Hallioglu et al, 2001). In one of these studies, Hallioglu et al found a decrease in alpha activity in the dominant temporal lobe and bilaterally in the frontal lobes.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In regard to the latter, readers may find it interesting that children in special education classes, which is a population we often see in neurotherapy, have more problems with nocturnal enuresis than other children (Spee van der Wekke, Hirasing, Meuhmeester, & Badder, 1998). I do not believe that neurofeedback practitioners have been aware that there are also some interesting QEEG studies on primary nocturnal enuresis (e.g., Kaada & Betvedt, 1981;Hallioglu et al, 2001). In one of these studies, Hallioglu et al found a decrease in alpha activity in the dominant temporal lobe and bilaterally in the frontal lobes.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…A delay in the maturation of sensory–motor neurons in the CNS, such as in the reticular formation, may cause a lack of awareness of bladder distension [28]. A study evaluating the relationship between ME and PE reported that the weak control of target organs by the cerebral cortex and the abnormal low threshold of sensory neurons in the intestine and genitalia may account for findings demonstrated in patients with PE, irritable bowel syndrome, or ME [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hallioğlu et al evaluated the maturation of the central nervous system with visual and quantitative electroencephalography (EEG). 15 They concluded that insufficient cerebral maturation was an important factor in the pathogenesis of PNE. Kohyama et al proposed that enuretic patients had dysfunctions in the pontine reticular formation.…”
Section: Discussionmentioning
confidence: 99%